Alveolar macrophages in pulmonary alveolar proteinosis: origin, function, and therapeutic strategies - Huang, Xinmei; Cao, Mengshu; Xiao, Yonglong (Frontiers in Immunology, 2023)
Pulmonary alveolar proteinosis (PAP) is a rare pulmonary disorder that is characterized by the abnormal accumulation of surfactant within the alveoli. Alveolar macrophages (AMs) have been identified as playing a pivotal role in the pathogenesis of PAP. In most of PAP cases, the disease is triggered by impaired cholesterol clearance in AMs that depend on granulocyte-macrophage colony-stimulating factor (GM-CSF), resulting in defective alveolar surfactant clearance and disruption of pulmonary homeostasis. Currently, novel pathogenesis-based therapies are being developed that target the GM-CSF signaling, cholesterol homeostasis, and immune modulation of AMs. In this review, we summarize the origin and functional role of AMs in PAP, as well as the latest therapeutic strategies aimed at addressing this disease. Our goal is to provide new perspectives and insights into the pathogenesis of PAP, and thereby identify promising new treatments for this disease.